PERLINDUNGAN HUKUM PEMEGANG SERTITIKAT HAK MILIK ATAS TANAH TERHADAP PEMBATALAN SERTIFIKAT TANAH (CONTOH PUTUSAN: NOMOR 10 PK/TUN/2020.) - margita, Susanto Agata (Gorontalo Law Review, 2024)
To find out "legal protection in the case of issuing a land certificate on another party's land, it must fulfill the requirements stipulated in the law and to know the legal consequences for the owner of land rights if there is a land certificate that has been issued by another party. In essence, there is a dispute between the parties regarding the object, namely the land plot. In this type of research, it is normative, namely legal research carried out by examining library materials or secondary materials with the approach used in this research being the statutory approach and the case approach method used in this research because it is the most appropriate approach method in solving legal issues. which is being studied." This dispute can be resolved through non-litigation or litigation.